Chapter Definizione e costruzione di una rete di Scuole che Promuovono Salute - Leporatti, Daniele (Studies on Adult Learning and Education, 2022)
Schools are able to make a significant contribution to students' health and well-being . This is widely recognised by international organisations, including the World Health Organisation (WHO), UNICEF, UNESCO, the US Centres for Disease Control and Prevention (CDC) and the International Union for Health Promotion and Education (IUHPE). The strategies and programmes that have been implemented worldwide over the past 20 years, have in common a comprehensive approach to schools, despite their differences. They recognise the fact that all aspects of school community life play an important role in health promotion. With this type of approach, it has become clear that it is not enough to include health education in the school educational offer. If schools are to fulfil their potential in promoting the health of the younger generations, the approach must be broader. In this context, the Regional School Office assumes a coordinating role, between the institutions and the different stakeholders, to implement the policies related to the Regional Prevention Plan and to the qualitative and quantitative description of the health of all subjects belonging to the school community in order to respond with guidance and governance tools to the needs of the different categories.